The Impermanent War Economy? Peace Dividends and Capital Accumulation in Israel - Jonathan Nitzan; Shimshon Bichler (The Political Economy of Middle East Peace. The Impact of Competing Trade Agendas, 1999)
The purpose of this article is to offer an alternative analytical framework for understanding the long term transformation in Israel. First, we argue against the conventional separation between the “political system” and the “economic system.” This separationist approach has been popular among Israeli scholars but its analytical value is open to doubt. Second, instead of the comment aggregate/statist approach, we take the disaggregate route of political economy, accentuating the historical role played by key power groups. And, finally, rather than focus merely on domestic considerations, we claim that both the earlier military economy and the current trajectory into “peace markets” are part of a broader global developments, particularly the internationalization of business institutions and the changing nature of the capitalist nation-state. In our opinion, the sharp “U-turn” in Israeli history is intimately linked to the changing nature of capital accumulation and corporate concentration, both in Israel and in the United States. For the large core firms at the centre of the economy, which we view as principal actors in this process, accumulation and concentration are two sides of the same process. With the evolution of modern capitalism, the leading firms are increasingly driven not to maximize their profits but rather to “beat the average.” Specifically, they seek to achieve a “differential rate of accumulation” – that is, to exceed the average rate of return in the economy. However, since a differential growth in profits implies control over a growing share of the aggregate capitalized assets, for these firms the goal of accumulation means a quest for rising corporate concentration.
Keywords: 330; arms; accumulation; acquisitions; capital; capitalism; centralization; competition; conflict; conglomeration; corporation; credit; crisis; debt; development; distribution; dual economy; elite; finance; globalization; growth; imperialism; distribution; IPE; Israel; labour; liberalization; M&A; merger; methodology; Middle East; military; national interest; security; oil; OPEC; ownership; Palestine; peace; politics; power; privatization; profit; ruling class; sabotage; stagflation; state; stock market; technology; TNC; United States; US; violence; war; Zionism